Des modèles pédagogiques devenus patrimoine artistique - Gilles Marseille (In Situ)
The School of Fine Arts of Nancy (now École nationale supérieure d’art et de design) bases its pedagogical practices on a collection of models that has been constantly evolving since 1793. Initially subordinate to the municipal museum, the teaching for drawing and modeling benefits from its proximity with important works from the Italian, Flemish and French schools. The collection of plaster casts built up at the same time was significantly enriched by loans from the Institut d’archéologie classique (université de Nancy) after 1918. The innovative principles of Art Nouveau also irrigate pedagogy, first by the purchase of Japanese works from 1891 and under the direction of Victor Prouvé, second president of the École de Nancy, during the inter-war period. The acquisition of some 6400 autochromes in the mid-1920s is the highlight of this period. In the aftermath of the Second World War, educational reforms relegated the ancient models in closets, basements and attics. The last two decades, on the contrary, are distinguished by the conservation, study and valorization of these collections (creation of an air-conditioned reserve, digitization programs, loans for exhibitions, new teaching uses).